2018
DOI: 10.1038/s41467-018-03850-4
|View full text |Cite|
|
Sign up to set email alerts
|

Rice auxin influx carrier OsAUX1 facilitates root hair elongation in response to low external phosphate

Abstract: Root traits such as root angle and hair length influence resource acquisition particularly for immobile nutrients like phosphorus (P). Here, we attempted to modify root angle in rice by disrupting the OsAUX1 auxin influx transporter gene in an effort to improve rice P acquisition efficiency. We show by X-ray microCT imaging that root angle is altered in the osaux1 mutant, causing preferential foraging in the top soil where P normally accumulates, yet surprisingly, P acquisition efficiency does not improve. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 35 publications
4
111
0
Order By: Relevance
“…Differences in PIN expression between trichoblast and atrichoblast cells lead to different auxin gradients between cell files and contribute to the site determination of root hair initiation (Balcerowicz et al, 2015). Likewise, AUX1 contributes to this auxin gradient and promotes root hair elongation in Arabidopsis and rice Giri et al, 2018…”
Section: Root Hair Developmentmentioning
confidence: 99%
“…Differences in PIN expression between trichoblast and atrichoblast cells lead to different auxin gradients between cell files and contribute to the site determination of root hair initiation (Balcerowicz et al, 2015). Likewise, AUX1 contributes to this auxin gradient and promotes root hair elongation in Arabidopsis and rice Giri et al, 2018…”
Section: Root Hair Developmentmentioning
confidence: 99%
“…We used these conditions as we found that osmotic stress on its own often leads to an increased percentage of root hairs that cease growing shortly after initiation, which strongly decreases the overall root hair length (Fig. 4), and because low Pi conditions are known to increase root hair formation of Arabidopsis and rice when grown in vitro (Bates and Lynch, 1996; Bhosale et al, 2018; Giri et al, 2018). We first assessed root hairs under low Pi only, so we were able to interpret the combined treatment.…”
Section: Resultsmentioning
confidence: 99%
“…To harden the X-ray beam, a 1.0 mm Cu filter was used. Recent studies on rice roots that involved X-ray CT have been listed in Table 2 [40,41,42,43,44,45,46]. Review of these studies indicated that most studies used pots with diameter < 100 mm and required scanning times of > one h. This indicated that our developed process flow is suitable for 4-D RSA phenotyping, when applied to rice showing relatively large RSAs.…”
Section: Discussionmentioning
confidence: 99%